Methamphetamine Use in a Bangladeshi Rehabilitation Center: Sociodemographic Patterns, Educational Associations, and Family Financial Burden - Chowdhury, Nisharga Meraj; Mosharop, Sharmin; Mahfuz, Syeda Mubashsharah; Islam, Saiful; Hossain, Mir Mubarak (British Journal of Healthcare and Medical Research, 2026)
Background: Methamphetamine use is an escalating public health challenge in Bangladesh, yet data from district-level rehabilitation settings remain scarce. This study examines sociodemographic patterns of substance use, the association between educational attainment and methamphetamine use, and the family financial burden of rehabilitation treatment among patients admitted to a rehabilitation center in Cumilla district. Methods: A cross-sectional, observational study was conducted at a purposively selected rehabilitation center in Cumilla district, Bangladesh, from October 28 to November 11, 2023. All 29 admitted patients were enrolled. Demographic, educational, occupational, and financial data were extracted from medical records. Descriptive statistics were used for analysis. Results: All 29 patients were male, predominantly aged 15–24 years (55.2%) and unemployed (62.1%). Methamphetamine (Yaba) was used by 34.5% of patients, with 80% of methamphetamine users being educated and 90% aged 15–24 years. Notably, all methamphetamine users were unmarried. Geographically, 75.8% of patients originated from Bangladesh-India border districts. The average treatment cost was approximately 9,000 BDT per month, constituting nearly 30% of the average family's monthly expenditure, with a mean rehabilitation stay of 64.5 days. Conclusion: Methamphetamine use is disproportionately prevalent among young, educated, unmarried males in border-adjacent districts of Bangladesh. The financial burden on families is substantial. Targeted health literacy programs and socioeconomic counseling should be integrated into substance use prevention and rehabilitation frameworks.